2018
DOI: 10.1002/dev.21799
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol secretion moderates the association between mother–infant attachment at 17 months and child behavior at age 5 years

Abstract: This study examined infant cortisol secretion as a moderator of the association between mother–infant attachment security at age 17 months and child behavior at age 5 years. A longitudinal community sample of 96 mother–child dyads participated in the strange situation procedure (SSP) at age 17 months. Cortisol was collected at baseline, and at 20 and 40 min post‐SSP. Maternal reports of child behavior were collected at age 5 years. Results revealed that the associations between nonsecure mother–infant attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 85 publications
(242 reference statements)
1
11
0
Order By: Relevance
“…Literature on neurophysiological correlates of attachment has flourished in recent years, but much of this work has focused, for example, on Gene x Environment research designs to determine what genetic factors influence pathways from insecure attachment to psychopathology [ 138 , 139 ] or has used endocrine mediators [ 140 ]. Assuming that both early attachment experiences and current attachments influence emotional regulation skills [ 49 ] and that emotional regulation is closely linked to psychopathological occurrence [ 141 , 142 ], creating a multi-layered search field from outside to inside, future research should more fully explore the connection with physiological measures, psychopathology and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on neurophysiological correlates of attachment has flourished in recent years, but much of this work has focused, for example, on Gene x Environment research designs to determine what genetic factors influence pathways from insecure attachment to psychopathology [ 138 , 139 ] or has used endocrine mediators [ 140 ]. Assuming that both early attachment experiences and current attachments influence emotional regulation skills [ 49 ] and that emotional regulation is closely linked to psychopathological occurrence [ 141 , 142 ], creating a multi-layered search field from outside to inside, future research should more fully explore the connection with physiological measures, psychopathology and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they vary depending on whether their results supported the differential susceptibility or the diathesis‐stress premises. One group of studies found that effects were stronger for individuals showing elevated baseline cortisol (Wagner et al, 2019) or cortisol reactivity (Bair‐Merritt et al, 2015; Hastings et al, 2011; Nofech‐Mozes et al, 2019; Saxbe et al, 2012) to psychosocial challenges. On the other hand, the risk of developing problem behaviors diminished remarkably for individuals with blunted cortisol responses (i.e., they demonstrated fewer health problems compared to their high‐reactive peers).…”
Section: Middle Childhood Parent–child Relationship Quality and Adolescent Healthmentioning
confidence: 99%
“…Taken together, there is a conflicting support in the literature for both differential susceptibility and diathesis‐stress models. A number of factors may attribute to these divergent findings, including variations in the type of rearing environments (Kuhlman et al, 2018) and subsequent health outcomes (Nofech‐Mozes et al, 2019), as well as the type of psychosocial and laboratory challenges used to induce stress and emotional responses. In their meta‐analysis, Bunea et al (2017) reported a moderate effect size across studies that examined the effects of childhood adversity on salivary cortisol responses to social stress.…”
Section: Middle Childhood Parent–child Relationship Quality and Adolescent Healthmentioning
confidence: 99%
See 2 more Smart Citations